DETERMINAN BREVET PAJAK SEBUAH PENDEKATAN MOTIVASI - Rosza, Rosza Dewanti; Hardiningsih, Pancawati (Jurnal Riset Akuntansi Politala, 2024)
The importance of a tax brevet for students is to increase students' academic capabilities and also open up greater opportunities in the world of work related to the field of taxation. This study aims to analyze and examine the effect of social motivation and career motivation moderated by economic motivation on tax brevet. The population of this study were accounting students at Stikubank University Semarang in 2019 and 2020. The sampling technique using purposive obtained as many as 181 students. The analysis technique uses Moderating Regression Analysis (MRA). The results of testing social motivation have a significant positive effect on tax brevets, career motivation has a significant positive effect on tax brevets, and economic motivation strengthens the influence of career motivation on tax brevets. These findings can be used for development both at the educational institution level, corporate level and government fiscal policy, so that students can keep up with tax regulation updates.